DEVELOPING SYSTEM DYNAMICS MODELS WITH "STEP-BY-STEP" APPROACH - Pejić-Bach, Mirjana; Čerić, Vlatko (Journal of Information and Organizational Sciences, 2007)
System dynamics is a powerful tool that enhances learning about company, market and competitors; portrays the cognitive limitations on the information gathering and processing power of human mind; facilitates the practice of considering opinions; and supports building of ";What if"; scenarios. Although the literature on system dynamics modeling is very rich with applications in many fields, not many papers on developing system dynamics models were published so far. In this paper we portray current approaches to the development of system dynamics models. These are (1) model development based on influence diagram, (2) model development based on the identification of resources and their states, (3) usage of generic structures for specific domain field, and (4) component strategy for the formulation of system dynamics models. Validation is an important issue that none of these approaches tackles. We propose a ";step-by-step"; approach that integrates validation with developing process of system dynamics models. This approach will be demonstrated on the example of development of a simple inventory model.